Towards a renewed perspective on teaching trade - Jahangir, Junaid (My University, 2023)
The objective in this paper is to provide a renewed perspective on teaching trade. The idea is to create a teaching module like the one offered by the CORE textbook that blends microeconomics and macroeconomics concepts to address globalization. Neoclassical textbooks are contrasted with heterodox ones to provide a comparative outlook on key themes on trade. Subject material from various textbooks is complemented with YouTube videos, game theory applications, and a nuanced graphical analysis on topical issues. Apart from tariffs and current account deficits, the issues of fair trade, environmental sustainability, and economic sanctions are considered to appeal to students.
Keywords: CORE text; trade; teaching economics